"Everything that makes the town happens during the festival": the construction of the meaning of place through festival practices - Kelemen, Petra (Array, 2011)
An interest in a sense of place, constructed through an active relationship with physical space, has directed scholars' attention to performance and the production of place meaning. The intention of this paper is to observe these processes in a particular cultural practice: a festival. On the example of Špancirfest, a street festival organized in the Croatian town of Varaždin, the author focuses on ways in which festival practices shape visitors' relations towards the urban space and conceptualize the meaning of place. The analysis includes, on the one hand, the significance attached to the festival in the town cultural politics, in which it functions as the holder of desirable attributes that position the town on the regional and the broader, global map. The emphasis on tradition, i. e. traditional crafts and baroque culture, which represented the festival core in its beginnings, has weakened over the years. At the same time, the festival becomes more associated with openness and multiculturalism, functioning as the image that community wants to send. The second part examines how people use the town space and how they attach meaning both to the festival and to the town. The central motives are the issues of belonging and identity construction, both the ones observed during the festival and those conceptualized in interviews conducted during the research. Therefore, the aim of the paper is to illuminate the role of the festival as a marker of place distinctiveness and as a significant element in the construction of a sense of place.